Antibacterial and Antiviral Properties of Coriandrum Sativum and Zingiber Officinale against Human Respiratory Tract Related Bacterial and Viral Infections: A Review with a Focus on the Case of SARS-CoV - Kodikara, Buddhi; Undugoda, Dr Lanka; Karunarathne, Himashi; Kandisa, Ravi (Advances in Technology, 2022)
Phytochemical constituents in extracts from medicinal plants have been widely used since ancient times to treat microbial infections. Coriandrum sativum and Zingiber officinale are two of the main popular ingredients in traditional medicine recipes. Currently, these extracts are used to prevent Covid-19 infections. Therefore, this review describes the antimicrobial properties of coriander and ginger and how far it is suitable to use against bacterial and viral infections occurring in the human respiratory tract. For instance, the main phytochemical available in C. sativum is linalool, followed by terpinene, pinene, cymene, decenal, and camphor. Gingerol is the main constituent in Z. officinale followed by shogaols and paradols. Moreover, many research findings revealed that the extract from coriander and ginger can be used to control respiratory tract infected pathogens due to the antiviral and antibacterial properties of available phytochemicals. Therefore, it is very effective to use coriander and ginger to boost the immune system. Furthermore, scientific evidence has proved the effective antiviral properties of compounds present in coriander and ginger that have binding affinity to the proteins in the virus, blocking the virus's receptors and boosting the immunity to face the COVID-19 situation. In fact, the effectiveness of the antimicrobial activity of mixed extract of medicinal plant parts is better than that of individuals. Therefore, this will review the therapeutic characteristics of coriander and ginger extracts due to their various phytochemical activities.